Studi Literatur Konteks Realistik Matematika pada Rumah Adat Suku Baduy (Aljabar : Jurnal Ilmuan Pendidikan, Matematika dan Kebumian, 2025)
This study aims to examine the potential of the Baduy traditional house as a realistic context in mathematics learning, particularly in the material of spatial geometry. The traditional houses of the Baduy people not only function as residences, but also hold cultural values, philosophies, and architectural structures rich in geometric elements. Using a systematic literature review (SLR) approach, this study explores various scientific sources, including journal articles, proceedings, and reference books, that discuss the relationship between spatial elements and the structure of traditional Baduy buildings. This approach was chosen so that the study obtained is comprehensive, directed, and able to illustrate the real contribution of ethnomathematics in learning. The results of the review indicate that the Baduy traditional house contains various forms of spatial geometry that can be clearly recognized, including cuboids, triangular prisms, pyramids, cubes, and cylinders. These elements are reflected in building components such as roofs, walls, floors, support pillars, and traditional household furniture. The visual and functional representation of these spatial geometry has the potential to be a contextual resource that can be utilized by teachers in the mathematics learning process, particularly through the Realistic Mathematics Education (RME) approach. By linking abstract mathematical concepts to local cultural phenomena, students not only gain a better conceptual understanding but also increase their active engagement, motivation to learn, and awareness of their own cultural identity. These findings emphasize the importance of utilizing local wisdom as an ethnomathematics approach that can provide meaningful, contextual learning rooted in the realities of students' daily lives. Through the integration of culture and education, mathematics learning can be more relevant, engaging, and support the preservation of national culture.